Environmental impacts of ice cream. (1st February 2019) - Konstantas, Antonios; Stamford, Laurence; Azapagic, Adisa
Abstract: Ice cream is consumed daily worldwide and yet its environmental impacts are scarcely known. This paper presents a first comprehensive life cycle assessment of market-leading vanilla and chocolate ice creams, considering both regular and premium products. The results suggest that their impacts are broadly similar across the 18 impact categories considered. For the majority of the impacts, chocolate regular ice cream is a slightly better option than the other varieties. Overall, the regular versions of the product have lower environmental impacts than the premium. Raw materials contribute most to the majority of impacts (>70%). The exception is ozone depletion, which is mainly due to refrigerated storage at the retailer (95%). The impacts are highly sensitive to the duration of storage and the type of refrigerant. Furthermore, the global warming potential of chocolate ice cream is very sensitive to land use change associated with cocoa beans cultivation, increasing the impact by 60%. Considering annual consumption of ice cream in the UK, the total primary energy demand contributes to 3.8% of energy consumption in the whole food sector while greenhouse emissions contribute 1.8%. Future improvements in the supply chain should focus on milk and cocoa production, reduced storage time and types of refrigerant used. Product reformulation to reduce the amount of milk (fat) and sugar should also be considered, in line with the emerging health-driven market trends. In addition to industry and policy makers, the findings of this study will be of interest to consumers, enabling them to make better choices with respect to environmental impacts of most popular ice creams.